Implementation of Project Based Learning Though Merdeka Curriculum in Teaching Speaking Skills - Rahmawati, Aulia Putri; Kusumaningtyas, Etika Dewi (English Education and Literature Journal (E-Jou), 2024)
Based on the phenomenon of new policy changes in Indonesian education, namely implementing an independent curriculum with the characteristics of a Project-Based Learning (PjBL) method. This study aims to describe teachers' perceptions in implementing Project Based Learning (PjBL) through Merdeka Curriculum using social media in teaching English speaking skills. The research design of this study is descriptive qualitative. The data collection of this research were interview, observation, and documentation. The data analysis technique used was Miles & Huberman (Display, Reduction, and Conclusion). The results showed that the implementation of Project-Based Learning (PjBL) through the Merdeka Curriculum in private vocational high schools has been implemented but not optimal because it has several obstacles related to implementation time, student motivation, and lack of facilities needed. However, the implementation of the Merdeka curriculum has a very good effect on teachers and students by implementing a learning process that focuses on students' ability to realize Speaking Skill teaching using Project Based Learning (PjBL) in accordance with the Merdeka Curriculum.